Pengaruh Peggunaan Alat Peraga Big Book terhadap Hasil dan Minat Belaar Peserta Didik - Siti Fatimah; Dedi Romli Triputra; Diah Sunarsih (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine the effect of the big book teaching aid on the learning outcomes and interest of third grade students at SDN Pebatan 02 and SDN Pesantunan 01, the material of folding symmetry and rotational symmetry. The method used in this study is a quantitative research type of experiment, with a pretest-posttest control group design research design. The sampling technique used in this research is saturated sampling. The research instrument was in the form of multiple choice questions for data collection on learning outcomes, and a questionnaire was used to collect data on interest in learning. This study was analyzed using the t test with the help of SPSS 22. The results obtained in this study are (1) descriptively there is a difference in the average value between the experimental class and the control class with the acquisition value of 74.55 and 63.14. The t-test of the learning outcomes obtained the value of sig. (2-tailed) is 0.021 < 0.050, so Ha is accepted and Ho is rejected. This the big book teaching aids have an effect on student learning outcomes. (2) Descriptively there is a difference in the average value between the experimental class and the control class with the acquisition value of 34.10 and 29.64. The results of the t-test of interest in learning obtained the value of sig. (2-tailed) of 0.002 < 0.050, so Ha is accepted and Ho is rejected. Thus, the big book props have an effect on students' learning interest.